A cinematographic fence and ornamental oars: experiencing the sublime in structures of urban public space - Ziegler, Denise (Approaching religion, 2016)
I approach the theme of the sublime experience in public urban space from the point of view of a visual artist and from one of a person walking through the city. In this essay a concrete sublime experience in public urban space is analysed through an experimental artistic intervention. In this way knowledge is gathered about the relationship between public urban space and its users. I engage in a dialogue with the ancient understanding of the sublime as an effect of elevated, performed language. Features of this rhetoric are adapted on to the visual appearance of public urban space in order to reveal situations that evoke sublime experiences.